Optimalisasi Peran Lembaga Keuangan Syariah dalam Inklusivitas Grand design Ekonomi Syariah di Tingkat Asia - Ichwan Arifin (Economic Reviews Journal, 2024)
We will not receive God's kindness if we obey him and eat and drink from what He has commanded us to consume or from what He has made lawful. Our efforts, however, will be in futile if we disobey Him and continue to eat and drink from what is illegal. When we discuss halal products, we are discussing halal food items and beverages. Products that meet the requirements for legitimacy under Islamic Shariah are referred to as halal products. Items that are suitable for use with food and drink include: First, steer clear of anything that contains or is produced from pork. For example: bristle brushes made of swine feathers, lard (pork fat), gelatin, lechitine, and emulsifiers (E471). QS. Al-Baqarah (2):173 contains it. Both meats are from halal animals that were killed in accordance with Islamic Shariah regulations. Al-Maaidah, QS. (5):3. 3. Any food or beverage that isn't made with alcohol or any of its byproducts, or that purposefully adds non-alcohol ingredients and isn't khamr. QS. Al-Maaidah (5):90, Al-Baqarah (2):219. The fourth is neither blood nor a corpse that is off-limits to human consumption. Al-Baqarah, QS. (2): 173. Including any and all foods acquired lawfully. Everything is allowed to be consumed, especially food and liquids. Eat what is righteous and excellent in the earth, men, and do not walk in Satan's footsteps, for he is clearly your enemy.Notwithstanding the ongoing unpredictability caused by the COVID-19 pandemic, Dinar Standard projects that the six actual sharia economy sectors—halal food and drink, modest fashion, cosmetics, pharmaceuticals, media and recreation, and travel—will account for 9.1% of the total growth in Muslim spending worldwide by 2022. By 2025, this growth is predicted to have increased by 7.5% to US$2.8 trillion. (CAGR)